The Effect of Skills, Work Motivation and Organizational Commitment Against Employee Productivity PT. Indomarco Prismatama Medan Branch Area Tanjung Morawa - Fadhilul Roji Nasution; Adrial Falahi (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effect of skills, work motivation and organizational commitment on the productivity of employees of PT. Indomarco Prismatama. This research uses a quantitative descriptive method, the population of which is the employees of the Indomaret store. The sampling technique for this research uses a Saturated Sample, so that the research sample is set at 100 people. The results of this study indicate that the multiple linear regression equation is obtained by the equation Y = .563 + 0.621 X 1 + 0.355 X 2 + 0.532 X 3 . The results of the t test obtained the value of t count = 8.545 > t table = 1.660 and a significance of 0.000 < 0.05, then Ha is accepted and Ho is rejected, which means that the Skills variable (X 1 ) partially has a significant effect on Employee Productivity (Y) PT. Indomarco Prismatama. The value of t count = 7.343 > t table = 1.660 and a significance of 0.004 <0.05, then Ha is accepted and Ho is rejected which means that the Organizational Commitment variable (X3) partially has a significant influence on Employee Productivity (Y) PT. Indomarco Prismatama. The results meaning that the variables of skills, work motivation and organizational commitment simultaneously have a positive and significant effect on Employee Productivity (Y).